2013
DOI: 10.1111/ddg.12173
|View full text |Cite
|
Sign up to set email alerts
|

A 36‐week retrospective open trial comparing the efficacy of biological therapies in nail psoriasis

Abstract: Biological therapies have shown to ameliorate psoriatic nail lesions. We did not find any statistically significant differences between the four biological drugs investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 22 publications
1
23
1
2
Order By: Relevance
“…Our results confirmed that NP is related to a longer duration of skin lesions and are in line with the subanalysis of the BELIEVE study . Our study also confirmed that the biological agents used (etanercept, ustekinumab, infliximab and adalimumab) were all equally effective in treating nail and skin psoriasis, as previously reported . In fact, the mean NAPSI score decreased from 18.53 at W0 to 2.83 at W24 (Fig.…”
Section: Discussionsupporting
confidence: 91%
“…Our results confirmed that NP is related to a longer duration of skin lesions and are in line with the subanalysis of the BELIEVE study . Our study also confirmed that the biological agents used (etanercept, ustekinumab, infliximab and adalimumab) were all equally effective in treating nail and skin psoriasis, as previously reported . In fact, the mean NAPSI score decreased from 18.53 at W0 to 2.83 at W24 (Fig.…”
Section: Discussionsupporting
confidence: 91%
“…It was, however, lower than that of people requiring treatment with biologic agents . The participants in our study had a mean DLQI score of 10.17 (7.46, 12.89), which corresponds to moderate to severe psoriasis . The mean DLQI score of our study subjects was found to be higher than that of participants in some studies (no statistical comparison) including a large German study that examined 4863 psoriasis patients .…”
Section: Discussionmentioning
confidence: 44%
“…Prior studies of the effects of biologic agents on nail psoriasis have varied substantially in study duration, population size and study design, making comparisons difficult . In addition, some studies have chosen scoring systems other than NAPSI to assess nail psoriasis .…”
Section: Discussionmentioning
confidence: 99%
“…Psoriasis in more visible locations, such as the scalp and nails, has a disproportionate burden and more profound impact on quality of life (QOL) . Several recent reports suggest that among patients with psoriasis, 41% to 77% have nail psoriasis . In addition to cosmetic concerns, many patients with nail psoriasis have reported associated pain, interference with daily activities and work productivity, and a great effect of their disease on health‐related QOL .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation